Water Structures Reveal Local Hydrophobicity on the In2O3(111) Surface - Chen, Hao; Blatnik, Matthias A. .; Ritterhoff, Christian; Sokolovic, Igor; Mirabella, Francesca; Franceschi, Giada; Riva, Michele; Schmid, Michael; Cechal, Jan; Meyer, Bernd; Diebold, Ulrike; Wagner, Margareta (ACS nano, 2022)
Clean oxide surfaces are generally hydrophilic. Water molecules anchor at undercoordinated surface metal atoms that act as Lewis acid sites, and they are stabilized by H bonds to undercoordinated surface oxygens. The large unit cell of In2O3(111) provides surface atoms in various configurations, which leads to chemical heterogeneity and a local deviation from this general rule. Experiments (TPD, XPS, nc-AFM) agree quantitatively with DFT calculations and show a series of distinct phases. The first three water molecules dissociate at one specific area of the unit cell and desorb above room temperature. The next three adsorb as molecules in the adjacent region. Three more water molecules rearrange this structure and an additional nine pile up above the OH groups. Despite offering undercoordinated In and O sites, the rest of the unit cell is unfavorable for adsorption and remains water-free. The first water layer thus shows ordering into nanoscopic 3D water clusters separated by hydrophobic pockets.
CRIS-Team Scopus Importer:2022-12-16
Keywords: ab initio molecular dynamics simulations; atomic force microscopy; density functional theory; indium oxide; temperature-programmed desorption; water adsorption; water on oxides